Exploring endometriosis before surgical treatment: unraveling pain, sexual function and quality of life patterns - Juliana Olavo Pereira; Jaime Kulak Junior (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective: To identify pain, sexual function, and quality of life patterns in women with endometriosis, taking into consideration the American Society for Reproductive Medicine (ASRM) classification for endometriosis. Methods: A cross-sectional study of quantitative descriptive nature was conducted, including women with surgical recommendation due to endometriosis. The Numeric Pain Rating Scale, Endometriosis Health Profile, and Female Sexual Function Index tools were used for data collection. Descriptive and frequency analysis were employed. Using the K-means algorithm, cluster analysis was performed to group participants based on response similarities. Results: 104 women with endometriosis were included with a median age of 35 years. The majority were classified as grade III (57.69%) and IV (25.96%) for endometriosis. There was a significant difference in the division of two clusters concerning ASRM, with ASRM IV women more frequently associated with Cluster B, while Cluster A being predominantly formed by ASRM III women. Cluster B showed significantly worse data for dyspareunia and dysuria pain levels and for all variables in the FSFI and EHP-30 instruments, except for infertility, which did not differ between the groups. Conclusion: ASRM classification is not directly related to clustering. Women diagnosed with endometriosis, mostly ASRM III and IV, exhibit two distinct patterns, with one group having worse pain, sexual function and quality of life scores compared to the other group. Infertility is a crucial aspect to study concerning the quality of life of women living with the disease and aspiring for motherhood irregardless of the clustering.